Design And Evaluation Of Mul Tip Articulate. Systems Prepared Using Sieving-Spheronisation And Extrusionspheronisation - Karim , Sabiha (2011)

(untitled)
Pelletised dosage forms can be prepared by different methods which, in general, are time consuming and labor intensive. The current study was carried out to assess the feasibility of preparing spherical pellets by sieving the wet powder mass followed by spheronisation. This method was compared with extrusion-spheronisation process in terms of physical characteristics and in-vitro dissolution profile of the developed fommlations. Dosej berbentuk pelet boleh disediakan melalui pelbagai kaedah yang biasanya memakan masa serta memerlukan tenaga kerja yang banyak. Kajian ini dijalankan untuk menilai kebolehlaksanaan penyediaan pelet bulat melalui tapisan jisim serbuk basah dan dikuti dengan proses sferonisasi. Kaedah ini dibandingkan dengan proses sferonisasi ekstrusi dari segi ciri-ciri fizikal and profil pelarutan in-vitro daripada rumusan yang dibangunkan.